SCALA: Towards a physical calibration of CALSPEC standard stars based on a NIST-traceable reference for SNIFS. Issue Volume 14:Issue A30(2018) (August 2018) - Küsters, D.; Lombardo, S.; Kowalski, M.; Aldering, G.; Boone, K.; Copin, Y.; Nordin, J.; Rubin, D.
Abstract : SCALA is a physical calibration device for the SuperNova Integral Field Spectrograph (SNIFS), mounted to the University Hawaii 2.2m telescope on Mauna Kea. For type Ia supernova (SN Ia) cosmology programs, an improved fundamental calibration directly translates into improved cosmological constraints. The aim of SCALA is to perform a fundamental calibration of the CALSPEC (Bohlin 2014) standard stars, which are currently calibrated relative to white dwarf model atmospheres.